Development of Creative Communicative Skills of Future Educators - Avazbek Artiqboyevich Davronov (Euro Asian Journal Publishing, 2023)
This article provides information on how important the development of creative communication skills of future pedagogues is in the process of mastering modern educational technologies, the importance of future pedagogues being able to establish effective communication with students and the team of pedagogues. passed. Some methods of developing creative communication skills are also explained.
Keywords: Communication; creativity; motivation